2021
DOI: 10.1093/plphys/kiab543
|View full text |Cite
|
Sign up to set email alerts
|

Rice Cell Division Cycle 20s are required for faithful chromosome segregation and cytokinesis during meiosis

Abstract: Chromosome segregation must be under strict regulation to maintain chromosome euploidy and stability. Cell Division Cycle 20 (CDC20) is an essential cell cycle regulator that promotes the metaphase-to-anaphase transition and functions in the spindle assembly checkpoint, a surveillance pathway that ensures the fidelity of chromosome segregation. Plant CDC20 genes are present in multiple copies, and whether CDC20s have the same functions in plants as in yeast and animals is unclear, given the potential for diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
1
1
0
Order By: Relevance
“…Full length AtCDC20.1 localised to the nucleoplasm ( Figure 5A ) and did not co-localise with an ER marker ( Figure 5B ) but with cytoplasmic RFP ( Figure 5C ) unequivocally indicating that AtCDC20.1-GFP was localised to nucleoplasm and cytoplasm. The observed subcellular localisation of full length AtCDC20.1-GFP ( Figure 5 ) was similar to the recently reported localisation of CDC20 from rice, where transient expression in rice protoplasts of CDC20-GFP fusions were mainly localised to the nuclei and to a lower extent in the cytoplasm ( Lin et al, 2022 ).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Full length AtCDC20.1 localised to the nucleoplasm ( Figure 5A ) and did not co-localise with an ER marker ( Figure 5B ) but with cytoplasmic RFP ( Figure 5C ) unequivocally indicating that AtCDC20.1-GFP was localised to nucleoplasm and cytoplasm. The observed subcellular localisation of full length AtCDC20.1-GFP ( Figure 5 ) was similar to the recently reported localisation of CDC20 from rice, where transient expression in rice protoplasts of CDC20-GFP fusions were mainly localised to the nuclei and to a lower extent in the cytoplasm ( Lin et al, 2022 ).…”
Section: Resultssupporting
confidence: 89%
“…Moreover, yeast and animals harbour a single copy of the Cdc20 gene, whereas plants generally have multiple copies ( Capron et al, 2003 ; Lima et al, 2010 ). Indeed, a thorough evolutionary study of Cdc20 gene expansion identified multiple Cdc20 genes in the Charophyceae, Klebsormidiophyceae, Zygnematophyceae , and land plant species, indicating a tendency of Cdc20 gene expansion during streptophyte evolution ( Lin et al, 2022 ) and suggesting that Cdc20 gene duplications within-species were common during land plant evolution ( Lin et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%